Strategi Kepemimpinan Kepala Madrasah dalam Meningkatkan Mutu Pendidikan di Madrasah Tsanawiyah (JMPI: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to analyze the leadership strategies of madrasa principals in improving the quality of education in Madrasah Tsanawiyah. The research employs a qualitative approach using a library research method by examining various relevant sources, including books, scholarly journals, and official documents. Data were collected through documentation techniques and analyzed using content analysis. The findings reveal that madrasa principals play a strategic role as leaders, managers, supervisors, motivators, and innovators in enhancing educational quality. The leadership strategies implemented include transformational, visionary, and participative approaches, which contribute to improving teachers’ performance and the effectiveness of the learning process. The success of these strategies is supported by qualified human resources, adequate facilities, and stakeholder involvement; however, several challenges remain, such as limited resources and resistance to change. Effective leadership of madrasa principals has a significant impact on improving teaching quality, teacher professionalism, quality culture, and students’ achievement. Therefore, adaptive and innovative leadership is essential in achieving sustainable educational quality. Keywords: Madrasa principal leadership, educational quality, leadership strategies, Madrasah Tsanawiyah